A Comparison of Incidence and Factors Associated with Postanesthesia Care Unit Complication in Adult and Paediatric Patients - A, Gnana Nisha Juliet.; V, Kalpana Devi; Gunasekaran, Janani; P, Divya Bharathi.; N, Seethalakshmi.; S, Keerthana. M. (Journal of Neonatal Surgery, 2025)
Background: A post-anaesthesia care unit (PACU) provides specialized treatment to patients following surgery. The PACU is staffed by competent nurses who recognize patient issues during postoperative and rapid management. The most common PACU complications were respiratory, cardiovascular, and hypothermia. Post-operative nausea and vomiting, as well as the central nervous system. This complication may differ between adult and paediatric patients, depending on ASA grade, age, medication history, anaesthetic agents, type of surgery, duration of operation, intraoperative blood loss, fluid administration, hemodynamic instability, and so on. In the post-anaesthetic care unit, measures are carried out to ensure that the patient is carefully treated following surgery, such as recognizing and treating early anaesthesia and surgery problems before they become life-threatening. Recovering from anaesthesia, decreasing surgical mortality, and delivering high-quality care. Methods: The study was conducted at A.C.S Medical College & Hospital in Chennai, with a quantitative technique and an observational study research design. Data collection and analysis were conducted on a sample of 100 patients (50 adult and 50 paediatric), utilizing questionnaires. The study excluded patients who were admitted directly to the ICU or ward. Result: This study had 100 participants, with 50% being paediatrics and 50% being adults. We found significant differences in various PACU complications criteria, including difficulty breathing, postoperative nausea and vomiting, and operation length (p-value > 0.05). The majority of cases were paediatric rather than adult. In the post-anaesthesia care unit, there was a significant difference in post-operative pain assessments between groups, type of anaesthesia, and insomnia following surgery (p-value > 0.05). Conclusion: This study compares the incidence of post-anaesthesia care unit complications in adult and juvenile patients. The findings clearly indicate that adolescent patients in the post-anaesthesia care unit were more problematic than adult patients. Based on our findings, we recommend the post-anaesthesia care unit team needs to develop area-specific institutional guidelines and protocols to improve the patients' quality of care and outcomes in post-anaesthesia care unit. Improved post-anaesthesia care for paediatric patients may reduce complications, length of hospital stays, and psychological distress.